Integrating corporate brands in cross-border acquisitions: Serial acquirer focus - Hakala, Miikka (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Previous literature indicates a lack of attention paid to the integration of corporate brands in cross-border acquisitions, which consequently serves as a motivation for this thesis. The purpose of this thesis is to study how companies integrate corporate brands in cross-border acquisitions. The emphasis is consequently on the factors to be taken into consideration in the integration process as well as on the roles of different stakeholders and on the challenges that companies are likely to face when integrating corporate brands in cross-border acquisitions. This study is conducted as a qualitative research. The theoretical background of this study draws on branding and M&A literatures and provides a framework for the research. The literature review is divided under two main chapters covering different aspects of acquisitions from a corporate brand perspective, brand integration strategies as well as stakeholder perspective and the role of culture in cross-border M&A brand integration. The collected empirical data, on the other hand, consists of expert interviews as well as other supportive materials provided by the interviewed companies. The empirical data is derived from several different cross-border acquisitions in the B2B markets, including several different companies and industries and thus provides a holistic picture of the process of integrating of corporate brands in cross-border acquisitions. Thematic analysis was used in the analysis of interview data. The findings of this study indicate that generally acquiring companies’ broader strategic guidelines dictate a specific brand strategy to be used in every acquisition. However, this study finds that rather than choosing a specific strategy, the method of implementing the given brand integration strategy has a major impact on the success of the integration. Additionally, timeline for strategy implementation was found to be crucial. Furthermore, the timeline should depend on the target company corporate brand’s recognition and level of establishment in its local market. This study also emphasizes the role of stakeholder communication as well as proactive management of the integration of corporate cultures in the process of integrating corporate brands in cross-border acquisitions.